Photocatalytic therapy via photoinduced redox imbalance in biological system - Kun Zhou; Lili Du; Rui Ding; Letian Xu; Shuai Shi; Siyuan Wang; Zaiyu Wang; Guoqing Zhang; Gang He; Zheng Zhao; Ben Zhong Tang (Nature Communications)
Abstract Redox balance is essential for sustaining normal physiological metabolic activities of life. In this study, we present a photocatalytic system to perturb the balance of NADH/NAD+ in oxygen-free conditions, achieving photocatalytic therapy to cure anaerobic bacterial infected periodontitis. Under light irradiation, the catalyst TBSMSPy+ can bind bacterial DNA and initiate the generation of radical species through a multi-step electron transfer process. It catalyzes the conversion from NADH to NAD+ (the turnover frequency up to 60.7 min−1), inhibits ATP synthesis, disrupts the energy supply required for DNA replication, and successfully accomplishes photocatalytic sterilization in an oxygen-free environment. The catalyst participates in the redox reaction, interfering with the balance of NADH/NAD+ contents under irradiation, so we termed this action as photoinduced redox imbalance. Additionally, animal experiments in male rats also validate that the TBSMSPy+ could effectively catalyze the NADH oxidation, suppress metabolism and stimulate osteogenesis. Our research substantiates the concept of photoinduced redox imbalance and the application of photocatalytic therapy, further advocating the development of such catalyst based on photoinduced redox imbalance strategy for oxygen-free phototherapy.